State enterprises : the emerging scenario - Batra, Satish K. 1944-; Jain, Tej K. 1946- (Jaipur : Printwell Publishers : Exclusive distributors, Rupa Books International, 1988)
Contributed articles; with reference to India.
Includes bibliographies and indexes.
Rashid
Keywords: Government business enterprises -- India